Bystander first aid in trauma – prevalence and quality: a prospective observational study. Issue 9 (19th June 2015) - Bakke, H. K.; Steinvik, T.; Eidissen, S.‐I.; Gilbert, M.; Wisborg, T.
<x xml:space="preserve">Abstract</x> Background Bystander first aid and basic life support can likely improve victim survival in trauma. In contrast to bystander first aid and out‐of‐hospital cardiac arrest, little is known about the role of bystanders in trauma response. Our aim was to determine how frequently first aid is given to trauma victims by bystanders, the quality of this aid, the professional background of first‐aid providers, and whether previous first‐aid training affects aid quality. Methods We conducted a prospective 18‐month study in two mixed urban–rural Norwegian counties. The personnel on the first ambulance responding to trauma calls assessed and documented first aid performed by bystanders using a standard form. Results A total of 330 trauma calls were included, with bystanders present in 97% of cases. Securing an open airway was correctly performed for 76% of the 43 patients in need of this first‐aid measure. Bleeding control was provided correctly for 81% of 63 patients for whom this measure was indicated, and prevention of hypothermia for 62% of 204 patients. Among the first‐aid providers studied, 35% had some training in first aid. Bystanders with documented first‐aid training gave better first aid than those where first‐aid training status was unknown. Conclusions A majority of the trauma patients studied received correct pre‐hospital first aid, but still there is need for considerable improvement, particularly hypothermia prevention. Previous first‐aid training seems to improve the quality of first aid provided. The effect on patient survival needs to be investigated.